PENGURANGAN INTENSITAS FLUKTUASI TEKANAN PADA PEMBESARAN MENDADAK ALIRAN UDARA – AIR SEARAH HORISONTAL DENGAN PENEMPATAN RING - Mustakim Mustakim; Indarto Indarto; Purnomo Purnomo (TURBO [Tulisan Riset Berbasis Online], 2012)
This research aims to reduce the effect of pressure fluctuations intensity on the sudden expansion of two phase flow of air - water in the same direction with the horizontal placement of the ring. Measurements done by installing a differential pressure transducer device that is placed on pressure points before and after sudden expansion. Output voltage signal recorded by a digital storage osciloscope. Tests conducted on water discharge 0.000038 m 3 / s; 0.000078 m 3 / s; 0.000116 m 3 / s; 0.000154 m 3 / s; 0.000198 m 3 / s; 0.000244 m 3 / s; 0.000284 m 3 / s and air flow 0.000065 m 3 / s; 0.00013 m 3 / s; 0.000195 m 3 / s; 0.000255 m 3 / s; 0.00032 m 3 / s; 0.000385 m 3 / s; 0.00045 m 3 / s. Results showed that if the total mass flow rate increases the pressure drop increases. Installation of the ring can reduce the pressure fluctuations intensity, the most effective installation of the ring using the ring the same diameter. Flow path is generally slug and plug flow pattern.